2024
DOI: 10.3390/photonics11040294
|View full text |Cite
|
Sign up to set email alerts
|

Realization of 4 × 200 Gbps 4-QAM OFDM-OWC System Using Higher Order OAM Modes for HAP-to-Satellites Scenario

Meet Kumari,
Satyendra K. Mishra

Abstract: Recently, there has been an increase in interest in using optical wireless communication (OWC) links on high-altitude platforms (HAPs) for satellite applications. We implement an orbital angular momentum (OAM) multiplexed orthogonal frequency division multiplexing (OFDM) system using an OWC link. A space-to-air scenario is considered in which transmission pointing errors, geometric loss, turbulence, and additional link losses are taken into account to extend the transmission range, system capacity, and through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This paper designs and investigates a satellite-ground-underwater OWC system based on OAM technology with 4 × 4 × 10 Gbps transmitting nodes. Based on the results of the analysis, it can be concluded that OAM using different LG modes offers significant benefits in all three scenarios within space, air, and the ocean for enhancing the range and quality of transmissions, the data rate, and the channel capacity [32]. With a BER of 10 −9 , a maximum satellite-to-ground transmission distance of 21,500-30,000 km can be achieved.…”
Section: Discussionmentioning
confidence: 97%
“…This paper designs and investigates a satellite-ground-underwater OWC system based on OAM technology with 4 × 4 × 10 Gbps transmitting nodes. Based on the results of the analysis, it can be concluded that OAM using different LG modes offers significant benefits in all three scenarios within space, air, and the ocean for enhancing the range and quality of transmissions, the data rate, and the channel capacity [32]. With a BER of 10 −9 , a maximum satellite-to-ground transmission distance of 21,500-30,000 km can be achieved.…”
Section: Discussionmentioning
confidence: 97%